SIMULTANEOUS DISSOLUTION OF HYDROXYLAPATITE AND PRECIPITATION OF HYDROXYPYROMORPHITE: DIRECT EVIDENCE OF HOMOGENEOUS NUCLEATION - Lower S.K.; Maurice P.A.; Traina S.J. (My University, 1998)
Results of in situ atomic force microscopy (AFM), ex situ AFM, optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, and x-ray diffraction were combined with previous macroscopic investigations to characterize aqueous Pb(NO3)2 reaction with hydroxylapatite (Ca5(PO4)3OH) (HAP). Experiments were conducted by immersing particulate HAP crystals in the AFM fluid cell in solutions with initial Pb concentrations = 100 mg L-1, at pH 6 and 22°C under static conditions. Experimental results showed that transport-controlled HAP dissolution provided phosphate for precipitation of hydroxypyromorphite (Pb5(PO4)3OH) (HPY), which in turn sequestered aqueous Pb. The combination of in situ and ex situ techniques provided direct evidence that HPY formed primarily by homogeneous nucleation in solution. Nevertheless, HPY needles were found in close association with HAP surfaces, most probably due to diffusional controls on phosphate concentrations. Diffusion of phosphate away from dissolving HAP appeared to be the rate-limiting step in the overall reaction sequence.